Sistem Management Data Perpustakaan Berbasis Web untuk Efesiensi Layanan Peminjaman di MTs Al-Falah Wujil - Wibisono, Iwan Setiawan; Rahman, Fitri Anisa (Jurnal Ilmiah Global Education, 2026)
The library has a strategic role in supporting the learning process within educational institutions, including at MTs Al-Falah Wujil. However, manual management often leads to inefficiencies such as delays in recording book loans and returns, difficulty in organizing collections, and a high risk of data loss. This study aims to design and develop a web-based library management system to improve the efficiency of lending services. The system was built using the PHP programming language and MySQL database with the Waterfall development model. Its main features include member registration, book collection management, QR Code-based attendance, borrowing and returning transactions, and automatic report generation. The system was tested using the Black Box Testing method to ensure that all functions operated correctly based on user input and output results. The testing results showed that the system improved lending efficiency by up to 70%, reduced human errors, and minimized data loss. Overall, the implementation of this system enhances library service performance and supports the improvement of educational quality at MTs Al-Falah Wujil.